Mediating role of dividend policy among its determinants and organizational financial performance - Ahmed Imran Hunjra (Cogent Economics & Finance, 2018)
The mediating mechanism of dividend policy remained untapped between financial performance, uncertainty, corporate social responsibility (CSR) and stakeholders' interest. However, this study contributes to the body of knowledge and discovers the mediating role of dividend policy between financial performance, uncertainty, CSR and stakeholders' interest. Data is collected through a questionnaire from CFO's/financial managers of Pakistani corporate sector. Structural Equation Modeling (SEM) is used to analyze the results through AMOS. Uncertainty, CSR, and stakeholders' interests have a significant impact on financial performance. It is found partial mediation between uncertainty and financial performance whereas dividend policy fully mediates the CSR, stakeholders' interest and financial performance.
Keywords: G20; G32; 330; CSR; stakeholder interest; financial performance; dividend policy; uncertainty; SEM